2016
DOI: 10.7717/peerj.1858
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation ofSchizosaccharomyces pombe α-actinin

Abstract: The actin cytoskeleton plays a fundamental role in eukaryotic cells. Its reorganization is regulated by a plethora of actin-modulating proteins, such as a-actinin. In higher organisms, α-actinin is characterized by the presence of three distinct structural domains: an N-terminal actin-binding domain and a C-terminal region with EFhand motif separated by a central rod domain with four spectrin repeats. Sequence analysis has revealed that the central rod domain of α-actinin from the fission yeast Schizosaccharom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, these studies have assumed that SpAin1 is a dynamic cross-linking protein that bundles F-actin with mixed orientations based on its similarity to other α-actinins and localization to the division site. Although SpAin1 was recently shown to bind and bundle F-actin ( Addario et al. , 2016 ), the quantitative behavior of SpAin1 on single and bundled actin filaments, the properties of SpAin1-mediated bundles, and whether these properties are critical for SpAin1’s roles in cytokinesis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have assumed that SpAin1 is a dynamic cross-linking protein that bundles F-actin with mixed orientations based on its similarity to other α-actinins and localization to the division site. Although SpAin1 was recently shown to bind and bundle F-actin ( Addario et al. , 2016 ), the quantitative behavior of SpAin1 on single and bundled actin filaments, the properties of SpAin1-mediated bundles, and whether these properties are critical for SpAin1’s roles in cytokinesis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to fimbrin Fim1, α-actinin Ain1 is a relatively weak F-actin bundling protein (Addario et al, 2016; Li et al, 2016; Morita et al, 2017). Remarkably, low-speed sedimentation (Figure 6A,B) and TIRFM assays (Figure 6C,D, Figure 6—video 1) revealed that tropomyosin Cdc8 significantly enhances the F-actin bundling ability of Ain1.…”
Section: Resultsmentioning
confidence: 99%
“…Coincidently, structural studies have indicated a regulatory interaction between CH1 and CH2 in mammalian α-actinin (41). The ABD of S. pombe Ain1 was also shown to form a similar structure (30). The R216E mutation, corresponding to the single point mutation H. sapiens α-actinin ACTN4 that causes a configurational change in two CHDs (42), caused the prominent accumulation of Ain1 in the middle region of mitotic cells, possibly by abrogating the interaction between CH1 and CH2 (31; Fig.…”
Section: Mechanism Of the Cr-specific Localization Of Ain1mentioning
confidence: 85%
“…Moreover, Ain1 appears to cooperatively promote the formation of the CR with myosin-II Myo2 (29). However, the biochemical and structural characterization of Ain1 had not been performed until recently (30,31). We herein evaluated the actin-binding activity of Ain1 using the recombinant protein.…”
Section: Introductionmentioning
confidence: 99%